LINC01798/miR-17-5p axis regulates ITGA8 and causes changes in tumor microenvironment and stemness in lung adenocarcinoma - Li, Xuanguang; Zhu, Guangsheng; Li, Yongwen; Huang, Hua; Chen, Chen; Wu, Di; Cao, Peijun; Shi, Ruifeng; Su, Lianchun; Zhang, Ruihao; Liu, Hongyu; Chen, Jun (Frontiers in Immunology, 2023)
Integrins are closely related to the occurrence and development of tumors. ITGA8 encodes the alpha 8 subunit of the heterodimeric integrin alpha8beta1 protein; very little literature on the mechanism of this gene in the occurrence and development of lung cancer is available. Through the public database, we found that the expression of ITGA8 in tumor tissue was significantly lower than that in normal tissue, especially in lung cancer, renal carcinoma, and prostate cancer. In lung adenocarcinoma, survival analysis revealed that patients with higher ITGA8 expression had a better prognosis. ITGA8 was positively related to immune checkpoints genes and immunomodulators genes, whereas B cell, CD4 + T cell, CD8 + T cell, neutrophil, macrophage, and dendritic cell infiltration had the same correlation. Moreover, ITGA8 was negatively related to cancer stemness. Through the online database, we predicted the miRNAs and lncRNAs that regulated ITGA8 and obtained the regulatory network of ITGA8 through the correlation analysis and the Kaplan–Meier survival analysis. Using quantitative real-time polymerase chain reaction and Western blot analyses, it was verified that LINC01798 regulated the expression of ITGA8 through miR-17-5p. Therefore, the regulatory network of ITGA8 may serve as a new therapeutic target to improve the prognosis of patients with lung cancer.